Optimalisasi Upaya Collaborative Governance dalam Pencegahan Perkawinan Anak di Kabupaten Sumenep - Aisyah Haris, Rillia; Anita, Anita (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
Children marriage has become a serious problem and has broad impacts socially, economically, educationally, on health and community welfare. The collaborative governance perspective is used as an alternative solution that can solve public problems with the involvement of multiple stakeholders, not just the government. This research aims to analyze the prevention of child marriage with a collaborative governance perspective to find alternative solutions that are applicable to all stakeholders involved. This research uses qualitative methods with interactive data analysis techniques. Data collection was carried out by interviews, observation, documentation and FGD with relevant stakeholders. The research results show that in Sumenep Regency there have been collaborative efforts to prevent child marriage through various activities such as socialization, education and mentoring. Collaborative governance still needs to be improved in order to produce integrated collaborative actions that can reduce the number of child marriages. An approach based on local wisdom is also important to prevent child marriage in Sumenep Regency.